The efficacy and safety of cold atmospheric plasma as a novel therapy for diabetic wound in vitro and in vivo. Issue 3 (13th March 2020) - He, Rui; Li, Qin; Shen, Wenqi; Wang, Tao; Lu, Huijuan; Lu, Junxi; Lu, Fendi; Luo, Ming; Zhang, Jiankang; Gao, Haiwei; Wang, Dong; Xing, Wanli; et al.
Abstract: Cold atmospheric plasma (CAP) is a group of various chemical active species, such as ozone and nitric oxide, generated by working gas. CAP was demonstrated to have an effect on tissue regeneration and wound healing. We conducted this study to evaluate the efficacy and safety of CAP as a novel therapy for diabetic wounds in vitro and in vivo. The plasma consists of ionised helium gas that is produced by a high‐voltage and high‐frequency power supply. Eight‐week‐old male db/db mice and C57BL mice were treated with helium gas (control group), 90s' CAP (low‐dose group), and 180s' CAP (high‐dose group). Mice were treated and observed for 2 weeks. Skin samples from around the wound and blood samples were collected. Our in vitro analysis included scratch wound‐healing assays by using human HaCaT immortalised human epidermal cells. After 14 days of treatment, CAP could obviously promote diabetic wound healing. Wound closure rates were significantly higher in the low‐dose group and high‐dose groups compared with the control group. Meanwhile, compared with the control group, the protein expression of IL‐6, tumour necrosis factor‐α, inducible nitric oxide synthase, and superoxide dismutase in two CAP groups significantly decreased, while the protein expression of vascular endothelial growth factor and transforming growth factor‐β in two CAP groups significantly increased (all P < .05); these data show good agreement with the change in mRNA level (all P < .05). In vitro, scratch wound‐healing assays showed that plasma treatment could effectively ensure healing within 3 minutes of exposure (all P < .05). In addition, no difference was found in histological observations of normal skin and the level of serum alanine transaminase, aspartate aminotransferase, blood urea nitrogen, creatinine, and white blood cells among the CAP groups and control group. CAP treatment for 3 minutes every day improves wound healing in diabetic mice by suppressing inflammation, reducing oxidative stress, and enhancing angiogenesis, involving several proteins signalling, and it is safe for the liver and kidney.